Pesantren as a Prototype of Education with a Deep Learning Approach - Maimun, Maimun; Hamdani, Hamdani; Listiana, Heni; Lape, Peter (Research Departement of Darullughah Wadda'wah International Islamic University Bangil, Pasuruan, 2025)
The discourse on the deep learning approach in education, initiated by the Minister of Education and Culture at the end of 2024, suggests that pesantren, with their unique patterns, have implemented this approach within their teaching traditions. This research aims to demonstrate that Pesantren Puncak Darussalam has applied the deep learning approach in its educational practices. The study employs a qualitative approach using a case study method at Islamic Education Puncak Darussalam in Poto’an Dajah, Palengaan, Pamekasan. The research sources include primary data obtained from interviews with ustadz and students, as well as secondary data that supports the primary data, which consists of documentation and relevant literature. Data collection involved interviews, observations, and documentation, while data analysis was conducted through data condensation, presentation, and conclusion drawing. The main finding indicates that Pesantren Puncak Darussalam shares a similar learning process pattern with the deep learning approach, reflected in the pillars of meaningful learning, mindful learning, and joyful learning. This is evidenced by critical, interactive, reflective, and enjoyable learning experiences using traditional methods such as sorogan, bandongan, and ikhtisyaf. It is hoped that this research will serve as a scholarly narrative demonstrating the superiority of pesantren as a prototype for the deep learning approach.